Tribological Performance of Composites Reinforced with the Agricultural, Industrial and Post-Consumer Wastes: A Review - Sydow, Zuzanna; Sydow, Mateusz; Wojciechowski, Łukasz; Bieńczak, Krzysztof (Materials, 2021)
Waste management is still one of the leading global challenges in the 21st century. From the European Union’s point of view, the Waste Framework Directive obliges businesses and households to recycle at least 55% of their municipal waste by 2025 and to reach 65% in 2035. Hence there is a great need to seek new solutions for the reuse of various waste materials. One of the most widely used wastes is their utilization as fillers or reinforcements in the metal- or polymer-based composites. The reuse of wastes for the production of tribological materials gives not only environmental benefits related to the transformation of waste into raw materials but also may improve the mechanical and tribological properties of such materials. Moreover, the use of waste reduces the production costs resulting from the lower price of filler materials and longer service life of developed products. The purpose of the current review is, therefore, aimed at the evaluation of the reuse of agricultural, industrial and postconsumer wastes as reinforcements in the composites used for tribological applications. The tribological performance (wear rate, coefficient of friction) of both monolithic and hybrid composites reinforced with waste materials was a particular subject of interest in this review.